2022
DOI: 10.1186/s12913-022-08673-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying technology to promote sexual and reproductive health and prevent gender based violence for adolescents in low and middle-income countries: digital health strategies synthesis from an umbrella review

Abstract: Aim Adolescents in low-and-middle-income countries (LMICs) are facing numerous developmental, sexual and reproductive health (SRH) challenges including exposure to multidimensional violence. Gender-based violence (GBV) specifically intimate partner violence (IPV) are both highly prevalent in LMICs and are strongly linked with poor SRH outcomes. However, GBV and IPV interventions have not yet been adequately integrated in SRH due to individual, social, cultural, service, and resource barriers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…This provides preliminary support for a peer-led model and/or testing of specific strategies to encourage the peer-to-peer transfer of knowledge. Peer-to-peer support/counseling has emerged as an effective delivery strategy for youth with mental health problems in a variety of high-and lowincome contexts [44][45][46][47][48]. If the process of sharing skills and information is perceived as offering mutual support from an "age mate" rather than lecturing or instructing from an elder, diffusion or sharing of skills may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…This provides preliminary support for a peer-led model and/or testing of specific strategies to encourage the peer-to-peer transfer of knowledge. Peer-to-peer support/counseling has emerged as an effective delivery strategy for youth with mental health problems in a variety of high-and lowincome contexts [44][45][46][47][48]. If the process of sharing skills and information is perceived as offering mutual support from an "age mate" rather than lecturing or instructing from an elder, diffusion or sharing of skills may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…This review qualitatively explored the experiences and perceptions of young peoples’ use of mobile phone platforms for SRH information and services in rural settings in LMICs using the GRADE-CERQual approach. Evidence has shown that mHealth technology platforms have the potential to address numerous SRH information and services access barriers for young people in rural contexts in LMICs (16, 18, 56-59). The study findings reported preferences and barriers for use of mHealth-based platforms for SRH information and services among rural young people across rural LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…For HIV, GBV, and SRH services, these strategies include community sensitization, gender empowerment, adolescent-and youth-friendly health services, and HIV testing (14,29). Comprehensively documenting and specifying implementation strategies can provide lessons on how the strategies facilitate realizing public health bene ts in the CHS (26), including promoting the uptake of health services (26,30,31).…”
Section: Introductionmentioning
confidence: 99%